Child Feeding Practices of Childbearing Mothers and Their Household Food Insecurity in a Coastal Region of Bangladesh - Md Abdullah Al Mamun; Shownak Saha; Jianfeng Li; Ruhina Binta A Ghani; Syed Mahfuz Al Hasan; Ayesha Begum (SAGE Publishing, 2022)
The current condition of ensuring WHO-recommended newborn and young child feeding practice is becoming a challenge in many developing nations, particularly in places where family food security is threatened. Because many households in underdeveloped nations frequently face acute food shortage due to poverty, optimal child nutrition is jeopardized. The purpose of this study was to analyze the child feeding behaviors of mothers with children aged 0-24 months and to investigate their household food insecurity in a coastal region of Bangladesh, Suborno Char (one of Noakhali District's coastal neighbourhoods) was studied from October 2019 to April 2020. In this study, a cross-sectional survey with multistage sampling technique was employed, and Suborno Char of Noakhlai district was purposely sampled of 400 women and their children aged 0-24 months. Data were obtained using a standard questionnaire and were analyzed using statistical functions in SPSS 20.0.0. Exclusive breastfeeding 53.5%, timely supplemental feeding 75.5%, and feeding children meals from homemade, canned/formula/fortified, both homemade and canned, milk these 4 food groups were at 22.2%. The moms' education level was strongly associated with their child feeding practices. Mothers from food insecure homes were less likely to exclusively breastfeed than mothers from food secure households after drawing interpretation of univariate & multivariate analysis of variables crude odds ratio (COR) and adjusted odds ratio (AOR) and confidence interval (CI) (COR .233 at 95% CI 0.083, .655 and AOR .478 at 95% CI 0.133, 1.713). Similar outcomes were seen for early complementary feeding and minimal dietary diversification of children. In conclusion, this study discovered a less dietary inclusion trend of child feeding practices among moms (0-24 months childbearing) in Bangladesh's coastal region.